(3cJGH aj UaGJ Gddg JYGdi heG hQO ajgG ef GdBi hGdCMGOjKs - (3eMeO Hf CMeO Hf CHj HcQ Hf aQM GdCfUGQj GdNRQLj GdCfOdSj, CHh YHO Gddg, GdbQWHj,J (B671 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO adeG PcQfG eGhbafG Ydjg ef CSeGA Gddg GdMSfi QCjJ Cf CVja EdjgG eeeG PcQg ef GdBi hGdCMGOjK GdJi LGA ajgG ef PcQ GdUaGJ s
(3BNQgG (B:s
(3hGdMhGOK dG Jchf UaI PGJ ddg JYGdi ced HMeO Gddg hYhfg s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B322 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B239s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds